The Role of Digital Coretax Technology in Enhancing Corporate Income Tax Compliance - Khusniah, Widatul; Merbaka, Zakiyyah Riris; Pahala, Indra; Wahono, Puji (The Future of Education Journal, 2025)
This study aims to examine the role of the Digital Coretax system in improving Corporate Income Tax (CIT) compliance in Indonesia. The methodology employed is a literature review by analyzing various academic sources, tax regulations, and official reports and publications from the Directorate General of Taxes (DGT). The findings indicate that the implementation of Digital Coretax has had a positive impact on tax administration efficiency, increased reporting transparency, and enhanced monitoring of corporate taxpayer compliance through digital-based data integration and risk analysis. However, challenges such as technological infrastructure readiness, users’ digital literacy, and inter-agency coordination still influence the system’s effectiveness. Therefore, this study concludes by emphasizing the importance of strengthening regulatory support, providing continuous education for taxpayers and tax officers, and optimizing system features to achieve sustainable tax compliance.